O trabalho da equipe do centro de atenção psicossocial álcool e outras drogas no atendimento às mulheres - Ciccilini, Mariane Fabiani (2015)
The consumption of licit and illicit drugs has increased in a considerable way among women, which becomes a great concern for the managers and a public health problem. Women have different physical characteristics that empower the harmful effects of psychoactive substance use, yonder the suffering of self-stigma, prejudice and stigmatization process by society. This fact demands from the health team the implementation of differentiated actions for this specific population. This study has the aim to analyze the perception of the health team from a CAPS AD from a city in the countryside of São Paulo state about their developed work towards a woman who uses alcohol and other drugs problematically. It is about a case study of qualitative method performed from November 2013 to March 2014, with 12 health professionals from a CAPS AD team, using semi-structured interviews, participant observation, and as analysis technique, the thematic content analysis. The study had as theoretical-interpretative framework the everyday and not everyday concept of Agnes Heller. Three thematic categories came up: development of the assistance work, development of the administrative and educational work and the difficulties on the everyday work with the women users. The results pointed the valorization of reception and qualified hearing activities by the health team, despite the predominance of assistance work be geared toward the male audience. The team’s meeting was a collective management strategy identified by the health professionals in the administrative dimension. In the educational scope the CAPS AD consisted on practical scenario of teaching and learning, strengthening the academics’ and health workers’ education. The main difficulties consisted on the material environmental and human conditions at CAPS AD, in the everyday work. The fragilities found in the organization’s network of psychosocial care of the city reflected on the development work of these professionals, creating physical and emotional overload. It was concluded that despite the prevalence of a pragmatic repetitious and alienated work, the health professionals could ponder discreetly about the work developed with the female audience.